A global study on the Life Cycle Assessment (LCA) of the modern cow leather industry - F. Brugnoli; K. Sena; L. Zugno; A. Oggioni (Discover Sustainability, 2025)
Abstract The leather industry lacks aggregated studies regarding the Life Cycle Assessment (LCA) of leather production. Existing studies to date are outdated, incomplete, use old methodologies, or do not represent the whole leather segment. There is a need for more complete, reliable, and updated studies in modern state-of-the-art leather production sites (tanneries), which are more representative of global leather production than the current limited and isolated studies. This work aims to provide an average LCA for the leather industry, without focusing on specific tanneries or locations. The goal is to produce high quality, up-to-date, and aggregated LCA data that accurately represents leather in comparison with synthetic and alternative materials. SimaPro 9.1.0.8 [1],a robust and reliable LCA software used to ensure the credibility of life cycle assessment results, and the Ecoinvent 3.6 [2] database, that features more than 2,200 new and 2,500 updated datasets, were used to conduct 56 LCA studies of bovine leathers produced by 6 leather groups in 16 facilities distributed among eleven countries (Argentina, Australia, Brazil, China, Italy, Sweden, Thailand, United Kingdom, the United States, Uruguay, and Vietnam) and for different types of leather (automotive, shoe, upholstery, and leather goods) that represent most types of leathers produced globally. The ISO 14044 [3] LCA methodology was used for LCA and life cycle inventory (LCI) studies providing the scope, interpretation, reporting, and critical review of the LCA. The LCA results indicate that, of the six impact categories studied (Global Warming, Eutrophication, Abiotic Depletion, Water Use, Water Consumption, and Freshwater Ecotoxicity), the farming stage (upstream) significantly contributes to the impact of five of them. A need for more basic data on raw material allocation, processing, and chemicals was identified. Nonetheless, the study revealed that the values for several parameters were much lower than previously indicated, particularly regarding allocation to raw materials. These new results can be used as a benchmark for complementary studies in this area and to recommend opportunities for process improvements that will make the leather industry more sustainable in the future. The paper contains important information for understanding the LCA hot spots and provides insights into the industry regarding the improvements needed in specific process areas. It also allows for a better understanding of data gaps that, when addressed, will allow for more reliable aggregated bovine leather LCAs.